Assessment of energy flows and energy efficiencies in integrated catalytic adsorption steam gasification for hydrogen production - Khan, Z. (Elsevier Ltd, 2018)
This study addresses the energy flows and energy efficiency of integrated catalytic adsorption biomass steam gasification for hydrogen production in a pilot scale bubbling fluidized bed system utilizing palm kernel shell as feedstock. The integrated catalytic adsorption utilizes catalyst and CO2 adsorbent together in the single fluidized bed gasifier. Various variables such as effect of temperature (600â750 Â°C), steam to biomass ratio (1.5â2.5 w/w), adsorbent to biomass ratio (0.5â1.5 w/w), fluidization velocity (0.15â0.26 m/s) and biomass particle size (0.355â0.500 to 1.0â2.0 mm) are investigated. The results imply that the overall requirement of gasification energy increases with increasing gasification temperature, steam to biomass ratio, fluidization velocity, and decreases with adsorbent to biomass ratio whilst no significant increase is observed by varying the biomass particle size. However, a slight reduction in required energy is observed from 600 Â°C to 675 Â°C which might be due to strong CO2 adsorption, an exothermic reaction, and contributes to the energy requirements of the process. Besides, hydrogen-based energy efficiencies increase with increasing temperature while first increases to a medium value of steam to biomass ratio (2.0), adsorbent to biomass ratio (1.0) and fluidization velocity (0.21 m/s) followed by a slight decrease (or remains unchanged). The integrated catalytic adsorption steam gasification is found to be a high energy consuming process and thus, waste heat integration needs to be implemented for feasible hydrogen production. Â© 2018 Elsevier Ltd